University Faculty, Colleagues and Teachers’ Federation as Mentors in Collaborative Action Research - Stagg Peterson, Shelley; Marks Krpan, Cathy; Swartz, Larry; Bennett, Jane (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
This research reports on collaborative research projects supported by a teachers’ federation. We compare research teams involved in the first year of the project, where they had free choice of research purposes with those in the second year who had the subject area defined for them. University faculty, teachers’ colleagues, and the teachers’ federation served as mentors for participating teachers. The action research resulted in change in teachers’ practice and in the development of leadership skills.